A “Light Bulb Moment” in Understanding Public Health for Undergraduate Students: Evaluation of the Experiential “This Is Public Health” Photo Essay Task - Dundas, Kate Joanne; Hansen, Vibeke; Outram, Suzanne; James, Erica L. (Frontiers in Public Health, 2017)
A lack of understanding of the importance of public health both within the community and in the tertiary education setting is a significant impediment to improvement in population health. The international campaign ‘This is Public Health’ (TIPH) has been promoted widely as a strategy to increase community awareness, and attract and inspire the next generation of public health professionals. This paper describes and evaluates student perceptions of a TIPH photo essay and reflective task in order to explore the pedagogical and learning outcomes related to undergraduate students' public health knowledge. The aim of the analysis was to understand 1) if the task led to increased awareness of public health, and if so, the process of how an understanding of public health develops, and 2) how the interactive nature of the experiential TIPH task leads to depth of understanding. This study was undertaken at the University of Newcastle (UON), NSW Australia. A qualitative study design using a descriptive case study methodology was employed. One-hundred and thirty-nine undergraduate students taking part in a semester-long, introductory public health course provided informed consent and completed a TIPH photo essay and reflective task as a compulsory assessment. Analysis of the student reflections was performed using a general inductive approach to qualitative thematic analysis. Analysis of the reflections indicated that completion of the photo essay and reflective task revealed two strong thematic clusters each with a number of sub themes. The most important findings were the six strong data clusters around students’ new and deeper understanding of Public Health. Additionally, four separate data clusters around the pedagogy of the task were revealed. The task also impacted beyond knowledge improvement and academic performance. Students alluded to an increased appreciation of their own health, a new recognition of the importance of preventative health measures, and an improved analytical awareness of health determinants and the measures in place to protect health. The TIPH photo essay and reflective task was successful in providing undergraduate students with an experiential activity that resulted in increased knowledge and understanding of public health strategies. The task was a valuable pedagogical experience.